PENGEMBANGAN CERITA BERGAMBAR DEANGAN KEARIFAN LOKAL BANYUWANGI BERBASIS WEBSITE UNTUK MENINGKATKAN KEMAMPUAN BERBICARA ANAK USIA 5-6 TAHUN RA PERWANIDHA SINGOJURUH - Qori'ah, Maria; Mutholifah, Lutfiyatul; Wanidha Andriani, Viena (Program Studi pendidikan Islam Anak Usia Dini, Fakultas Tarbiyah Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2025)
Abstract Illustrated story media with Banyuwangi local wisdom based on a website is a story media that contains characters from Banyuwangi. Illustrated stories stimulate children because they contain pictures and writing that arouse children's interest and curiosity about the contents of the illustrated story. This study aims to determine the feasibility, practicality, and effectiveness of illustrated stories with Banyuwangi local wisdom based on a website to improve the speaking skills of children aged 5-6 years. The subjects used were 25 children aged 5-6 years at RA Perwanida Singojuruh. This study is a type of Research and Development research with the ADDIE model. The data collection process carried out by researchers using three methods, namely questionnaires, observation and documentation. For data analysis using the SPSS test. The results of this study are the feasibility of the illustrated story product with Banyuwangi local wisdom based on a website obtained a value of 76.27% with the data interpretation category